Cost-effectiveness of video-observed therapy for ambulatory management of active tuberculosis during the COVID-19 pandemic in a high-income country. (December 2021) - Fekadu, Ginenus; Jiang, Xinchan; Yao, Jiaqi; You, Joyce H.S.
Highlights: The USA is a high-income country with a low tuberculosis (TB) burden. The coronavirus disease 2019 pandemic suspended directly observed therapy (DOT) for patients with TB. Suspension of DOT worsened treatment outcomes and increased the cost of TB. Video-observed therapy was cost-effective for TB during the pandemic in the USA. ABSTRACT: Objective: The coronavirus 2019 (COVID-19) pandemic caused suspension of directly observed therapy (DOT) for patients with active tuberculosis (TB). This study aimed to estimate the outcomes of pandemic-related DOT suspension and the cost-effectiveness of video-observed therapy (VOT) during the pandemic. Methods: A decision-analytic model was constructed to project outcomes of adult patients with active TB from the perspective of a US healthcare provider. Two model-based analyses were conducted: (1) before (with DOT) and during [with self-administered therapy (SAT)] the pandemic; and (2) VOT vs SAT during the pandemic. The primary outcome measures were direct medical costs and disability-adjusted life years (DALYs). Results: In the base-case analysis, care during the pandemic (with SAT) increased the cost (by US285 per patient) and DALYs (by 0.2155 per patient) in comparison with DOT. Care with VOT reduced DALYs (by 0.4870) and costs (by US1797) in comparison with SAT. On probabilistic sensitivity analysis, care during the pandemic (with SAT) increased DALYs in 100% of 10, 000 simulations, and increased costs in 55.52% of instances. Care with VOT reduced DALYs and costs in 99.7% and 68.79% of instances, respectively. The probability of VOT being cost-effective was 99.4% at the willingness-to-pay threshold of 50, 000 US/DALY. Conclusion: Suspension of DOT during the COVID-19 pandemic worsened treatment outcomes. VOT was found to be a cost-effective option for active TB care in an outpatient setting.